2021
DOI: 10.1021/acs.molpharmaceut.0c01183
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Receptor 5 Targeted Nanoparticles Imaging the Progression and Regression of Atherosclerosis Using Positron Emission Tomography/Computed Tomography

Abstract: Chemokines and chemokine receptors play an important role in the initiation and progression of atherosclerosis by mediating the trafficking of inflammatory cells. Chemokine receptor 5 (CCR5) has major implications in promoting the development of plaques to advanced stage and related vulnerability. CCR5 antagonist has demonstrated the effective inhibition of atherosclerotic progression in mice, making it a potential biomarker for atherosclerosis management. To accurately determine CCR5 in vivo, we synthesized C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…[ 64 Cu]Cu-DOTA-DAPTA-Comb were tested both in an ApoE –/– mouse model and in human carotid endarterectomy specimens. In the ApoE –/– mouse model, results showed sensitive and specific detection of CCR5 in plaques not only along the progression of atherosclerotic lesions, but also during plaque regression and the human ex vivo experiment, which confirmed the potential of CCR5 targeting in human atherosclerosis [ 73 ].…”
Section: Current and Emerging Nuclear Probes For The In Vivo Molecular Imaging Of Vascular Inflammationmentioning
confidence: 80%
“…[ 64 Cu]Cu-DOTA-DAPTA-Comb were tested both in an ApoE –/– mouse model and in human carotid endarterectomy specimens. In the ApoE –/– mouse model, results showed sensitive and specific detection of CCR5 in plaques not only along the progression of atherosclerotic lesions, but also during plaque regression and the human ex vivo experiment, which confirmed the potential of CCR5 targeting in human atherosclerosis [ 73 ].…”
Section: Current and Emerging Nuclear Probes For The In Vivo Molecular Imaging Of Vascular Inflammationmentioning
confidence: 80%
“…Promising results from PET studies using [ 68 Ga]pentixafor ( 14), [ 64 Cu]DOTA-ECL1i (1), and [ 64 Cu]DOTA-DAPTA-comb (5) expanded the boundaries of cancer and cardiac disorder imaging for CXCR4, CCR2, and CCR5, respectively. In addition, [ 64 Cu]Cu@CuO x -ECL1i-Gem [103] and [ 177 Lu]pentixather [146] may aid the development of suitable theranostic agents for the treatment of chemokine-related cancers. It is important to note that antibody-based PET radiotracers (immunoPET) have garnered attention in recent years because of their superior target specificity and ability to selectively image immune cells and inflammatory processes [147].…”
Section: Discussionmentioning
confidence: 99%
“…D-Ala1-peptide T-amide (DAPTA) is a synthetic CCR5-specific octapeptide (D-Ala-Ser-Thr-Thr-Thr-Asn-Tyr-Thr-NH 2 ) that inhibits the entry of HIV with 0.1 nM antagonist activity [101]. In 2014, Luehmann et al, developed a Cu-64-labeled DOTA-DAPTA ([ 64 Cu]DOTA-DAPTA, 4, Figure 2) and a Cu-64-labeled DOTA-DAPTA-comb nanoparticle (5) [102,103]. The DOTA-DAPTA-comb nanoparticle is a block copolymer of poly(methacrylate) whose ester groups were conjugated to PEG and PEG-DAPTA.…”
Section: Ccr5 Pet Radiotracersmentioning
confidence: 99%
“…Various studies have observed that inhibition of CCR5 reduces the production of inflammatory cytokines [ 44 , 45 ] and atherosclerosis [ 46 ]. Therapeutic targeting of CCR5 facilitates the control of inflammatory situations, especially in the context of cardiac complications.…”
Section: Discussionmentioning
confidence: 99%